The politics of memory in postwar Europe - Lebow, Richard Ned 1942- Hrsg; Kansteiner, Wulf 1964- HerausgeberIn; Fogu, Claudio 1963- HerausgeberIn (Duke Univ. Press, 2006)
The memory of politics in postwar Europe / Richard Ned Lebow -- From victim myth to co-responsibility thesis : Nazi rule, World War II, and the Holocaust in Austrian memory / Heidemarie Uhl -- The legacy of World War II in France : mapping the discourses of memory / Richard J. Golsan -- Losing the war, winning the memory battle : the legacy of Nazism, World War II, and the Holocaust in the Federal Republic of Germany / Wulf Kansteiner -- Italiani brava gente : the legacy of fascist historical culture on Italian politics of memory / Claudio Fogu -- New threads on an old loom : national memory and social identity in postwar and post-communist Poland / Annamaria Orla-Bukowska -- What is so special about Switzerland? Wartime memory as a national ideology in the Cold War era / Regula Ludi -- Past as present, myth, or history? Discourses of time and the great fatherland war / Thomas C. Wolfe -- The politics of memory and the poetics of history / Claudio Fogu and Wulf Kansteiner